2013
DOI: 10.4103/1450-1147.136739
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myofibroblastic Tumor of the Lung: Unusual Imaging Findings

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm, most commonly seen in children and adolescents. It can occur in nearly every part of the body. Imaging properties and the clinical presentation of IMT can mimic malignant process. A 41-year-old female presented with cough of 3 months duration. Chest X-ray showed a coin shadow in the right upper lobe. Positron emission tomography/computed tomography scan showed a 3.2 × 2.4 cm lesion with homogeneous appearance with a very high fluorodeoxyglucose uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…IMT, which is a rare tumor of mesenchymal origin, can be seen in nearly everywhere in the body [8]. Macroscopic findings of our case suggested that it may have been resulted from RIPV (Figure 3).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…IMT, which is a rare tumor of mesenchymal origin, can be seen in nearly everywhere in the body [8]. Macroscopic findings of our case suggested that it may have been resulted from RIPV (Figure 3).…”
Section: Discussionmentioning
confidence: 68%
“…Macroscopic findings of our case suggested that it may have been resulted from RIPV (Figure 3). No matter where it originates from, the main treatment of IMT is surgical excision [1][2][3]8]. The efficiency of nonsurgical treatments has not been established [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, these lesions may be parenchymal or endobronchial. Considered cellularly benign, they rarely invade the mediastinum, but can impinge on nearby structures . These lesions also have the potential to recur, which is thought to be due primarily to incomplete resection …”
Section: Discussionmentioning
confidence: 99%
“…Though there are case reports of complete resolution of inflammatory pseudotumors of the lung with pharmacotherapy, complete surgical resection remains the most frequently recommended course of treatment . Resection is performed both to exclude malignancy and to achieve cure as local expansion can cause morbidity . If the lesion is unable to be completely resected, cannot be resected due to location or size, or in the case of multifocal disease, reported treatments have included radiotherapy, chemotherapy, and corticosteroids .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation